DISEMINASI PERAKITAN INDUK UDANG GALAH SUMBER GENETIK BARITO DAN PRODUKSI BENIH PADA KELOMPOK PEMBENIHAN RAKYAT DENGAN POLA COOPERATIVE BREEDING SYSTEM - Yulius Kisworo; Anny Rimalia; Mukhlisah Mukhlisah (EnviroScienteae, 2016)
Dissemination of the parent assembly giant freshwater prawns and fry prawns Production was held on Bumi Temposo Group and Selatan Makmur Group on Sepunggur Southern Sub-District of Kusan Hilir, Tanah Bumbu of South Kalimantan. The method used in the application of science and technology are Participatory Rural Appraisal (PRA) with the pattern of the cooperative breeding system (CBS). Assembling Parent done by the multiplication of Parent of giant freshwater prawn through fry  production of selected conformed to protocol assembling followed production of prawns SNI: 01-2.6486.1-2 2000. The results of evaluation obtained a change in attitude and knowledge of the assembly stem and fry prawns production of prawns as a result of changes do not really know be learned or understood by 40% and Very Understood by 60% and this change of attitude significantly statistically.